Orthogonal Frequency-Division Multiplexing-Based Cooperative Spectrum Sensing for Cognitive Radio Networks - Arief Marwanto; Sharifah Kamilah Syed Yusof; M. Haikal Satria (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2014)
The detection of transmitted data collusion among sensing nodes needs to be resolved at data link layer. It takes a lot algorithm calculation effort and time constraint. A new method to sense the performance of cognitive radio (CR) by avoiding interference based on new master node (MN) algorithm. Interference could be reduced significantly by using only PHY (physical) information of the cognitive radio network. It saves a lot computational on above layer and detect the collusion of transmitted data as early as possible. By using a novel MN algorithm at PHY layer, it reduces the cost of computation and time to detect and avoid collusion of transmitted data.